The impact of innovation on globalization - Shao, Binhong (Brill, 2021)
"The Impact of Innovation on Globalization is the eighth volume of the series China in the World. Like other volumes in the series, this volume includes views of leading Chinese scholars on China's relations with other countries and regions in the world. In view of the theme of "globalization" in this volume, the contributors in this volume pay attention to how the Covid-19 pandemic impacts and challenges globalization, especially how it affects China, the United States, and their mutual relations. However, this is not to say that some issues surrounding globalization-the orientation and interrelationship of political and economic decision-making in China and the United States-have emerged only after the outbreak of the pandemic. The volume focuses on some long-term trends and innovations, from the past to the future. Chapter 2, "Globalization, Convergence, and China's Economic Development," describes the patterns of globalization. Chapter 3, "The Rejuvenation of the Chinese Nation is Unstoppable," talks about views on current economic and financial issues. Chapter 4, "Reconstructing Global Industrial Chains under the Pandemic, and China's Response," discusses China's pivotal position in global supply chains. Besides answering these basic questions, the book investigates other important issues, such as Global Value Chains, Changes in the International Order, Changes in the International Economic Landscape, WTO Reform, China's Foreign Economic and Trade Strategies, Towards a Climate Resilience Society, Identity Politics, and the AI "Revolution""-- Provided by publisher.
Keywords: Globalization -- China -- History -- 21st century.; International economic relations.; Technological innovations -- China -- History -- 21st century.; China -- Foreign relations -- 21st century.